Chemical antagonism between photodynamic agents and chemotherapeutics: mechanism and avoidance. Issue 92 (3rd November 2017) - Meng, Qingshuo; Meng, Jia; Ran, Wei; Su, Jinghan; Yang, Yuguang; Zhang, Pengcheng; Li, Yaping
Abstract : We report chemical antagonism between photodynamic agents and chemotherapeutics and provide a solution to turn antagonism into synergism. Abstract : We report a photochemical reaction-induced antagonism between the photodynamic agent (PS) and anti-cancer drugs during combined therapy. The annihilation of singlet oxygen and alkene-containing drugs into inactive drug hydroperoxides is responsible for the antagonism, and results in decreased efficacy against several cancer cell lines. Experimental and simulation results reveal that the annihilation abates with increasing distance between the PS and drugs via confining the PS and drugs into separated vehicles. As a result, antagonism can be switched to synergism in treating both drug sensitive and resistant cancer cells.